Flavonoid Identification and Antioxidant Activity of Graded Extracts from Kesambi (Schleichera oleosa) Leaves - Hanifah, Vika; Febrina, Dina; Rahmawati, Nur (Jurnal Mandala Pharmacon Indonesia, 2025)
Flavonoids are secondary metabolites widely distributed in plants and are recognized for their antioxidant potential, which plays a vital role in neutralizing free radicals and protecting against oxidative stress. Schleichera oleosa (kesambi) leaves are known to contain bioactive compounds, yet comprehensive studies on their flavonoid composition and antioxidant activity remain limited. This study aimed to identify flavonoid groups present in graded extracts of kesambi leaves and to evaluate their antioxidant activity. Graded maceration was performed sequentially with solvents of increasing polarity (n-hexane, ethyl acetate, and methanol). Flavonoids were identified through colorimetric reactions using specific reagents, while antioxidant activity was determined using the DPPH radical scavenging assay, with IC?? values calculated by linear regression. The results showed that n-hexane extract contained flavanones, ethyl acetate extract contained flavones, isoflavones, and flavonols, while methanol extract contained chalcones and aurones. Antioxidant testing revealed that methanol extract exhibited the strongest activity (IC?? = 9.65 ± 0.81 ppm), categorized as very strong, whereas ethyl acetate (IC?? = 102.46 ± 6.82 ppm) and n-hexane (IC?? = 141.67 ± 15.74 ppm) showed moderate activity. These findings confirm that solvent polarity greatly influences both flavonoid composition and antioxidant potency, with methanol extract emerging as the most promising natural antioxidant source. The study provides scientific support for the traditional use of kesambi leaves and highlights their potential for pharmaceutical and nutraceutical applications.